1886. Provider's Close Approximation of Parental Desire for Antibiotics Does Not Diminish Concern of Anticipated Conflict. (26th November 2018) - Myers, Angela; Hurley, Emily; Bradley, Andrea; Lee, Brian R; Newland, Jason; Bickford, Carey; Pina, Kimberly; De Miranda, Evelyn Donis; Mackenzie, Alexander; Goggin, Kathy
Abstract: Background: Pediatric providers cite parental pressure as a reason for antibiotic overprescribing for acute respiratory tract infections (ARTI). Previous work indicates providers overestimate parental desire for antibiotics. We examined providers' beliefs about parental interest in antibiotics, their comfort explaining denial and their concerns about parents' response. Methods: Providers and parents of children aged 1–5 years with ARTI were enrolled from an academic and private practice clinic in a RCT testing interventions to improve appropriate antibiotic prescribing. At baseline, providers rated their belief of how often parents want antibiotics for their children in the context of a viral illness (never/rarely/sometimes/often/always), comfort explaining denial of antibiotics, and concern about parental disagreement about antibiotic necessity (not at all/ somewhat/mostly/completely). Prior to intervention, parents rated their interest for an antibiotic for their child on a 1–100 visual analog scale; low (≤39), neutral (40–59) or high (≥60). Results: 41 providers [66% physicians/34% APN, 78% female, median 8 (IQR 4, 12) years in practice] and 1, 051 parents [mean age 31.5(SD = 6.0), 83.8% female, 26.0% ≤ high school degree, 80.0% White] were surveyed. Providers reported that parents sometimes (58%) or rarely/never (15%) want antibiotics. Similarly, the majority of parents' interest was neutral (61.3%) or low (10.4%). Although 98% of providers reported being mostly/completely comfortable explaining denial of antibiotics, 56% were concerned that parents would disagree and feared parental push back (74%) or lack of satisfaction with the visit (82%). Conclusion: Findings suggest that provider perceptions of parental desire for antibiotics are more tempered than previous reports and similar to what parents actually report. Nevertheless, despite high reported comfort explaining antibiotic denial, many providers still anticipate conflict when they tell parents that an antibiotic is not necessary. Disclosures: B. R. Lee, Pfizer: Investigator, Research grant. Merck: Investigator, Research grant. J. Newland, Merck: Investigator, Research grant. C. Bickford, Teva: Spouse's contract, Consulting fee.